Iodide Enhances the Production of Pseurotin D over Pseurotin A by Inverting the Preference for the SN2 versus the SN2′ Product in the Final Nonenzymatic Step - Choi, Yukyung; Kim, Yeongseo; Cha, Jin Wook; Lee, Gyu Sung; Pham, Huong T.; Ngo, Men Thi; Kim, Saegun; Kim, Chung Sub; Kang, Kyo Bin (American Chemical Society, 2025)
Nonenzymatic reactions, though critical in natural product biosynthesis, are significantly challenging to control. Adding 3% NaI to the culture medium of Penicillium janczewskii significantly increased pseurotin D (1) production and decreased pseurotin A (2) production. Previously, 1 and 2 were suggested to be produced via a nonenzymatic reaction, where the epoxide at C-10 undergoes SN2 (2) or SN2 ' (1) reactions. We confirmed that 1 was isolated as a 1:1 mixture of C-13 epimers by spectral elucidation via CP3 analysis aided by selective excitation NMR methods, which supported that 1 was produced through a nonenzymatic SN2 ' reaction. We propose that NaI increased the ratio of 1 by causing steric hindrance at the C-11 position of the transient intermediate, which makes C-13 more preferred in the SN2/SN2 ' competition.